CaV3.2 KO mice have altered retinal waves but normal direction selectivity - Hamby, Aaron M. (Vis Neurosci, 2015)
Early in development, before the onset of vision, the retina establishes direction-selective responses. During this time period, the retina spontaneously generates bursts of action potentials that propagate across its extent. The precise spatial and temporal properties of these “retinal waves” have been implicated in the formation of retinal projections to the brain. However their role in the development of direction selective circuits within the retina has not yet been determined. We addressed this issue by combining multi-electrode array and cell-attached recordings to examine mice that lack the CaV3.2 subunit of T-type Ca(2+) channels (CaV3.2 KO) because these mice exhibit disrupted waves during the period that direction selective circuits are established. We found that the spontaneous activity of these mice displays wave-associated bursts of action potentials that are altered from control mice: the frequency of these bursts is significantly decreased and the firing rate within each burst is reduced. Moreover, the retina’s projection patterns demonstrate decreased eye-specific segregation in the dLGN. However, after eye-opening, the direction selective responses of CaV3.2 KO DSGCs are indistinguishable from those of wild-type DSGCs. Our data indicate that, although the temporal properties of the action potential bursts associated with retinal waves are important for activity-dependent refining of retinal projections to central targets, they are not critical for establishing direction selectivity in the retina.